A Motivational-Developmental Free Response Assessment Through a Bifactor Lens - Alpizar, David; French, Brian F. (Frontiers in Psychology, 2021)
The Motivational-Developmental Assessment (MDA) measures a university student’s motivational and developmental attributes by utilizing overlapping constructs measured across four writing prompts. The MDA’s format may lead to the violation of the local item independence (LII) assumption for unidimensional item response theory (IRT) scoring models, or the uncorrelated errors assumption for scoring models in classical test theory (CTT) due to the measurement of overlapping constructs within a prompt. This assumption violation is known as a testlet effect, which can be viewed as a method effect. The application of a unidimensional IRT or CTT model to score the MDA can result in imprecise parameter estimates when this effect is ignored. To control for this effect in the MDA responses, we first examined the presence of local dependence via a restricted bifactor model and Yen’s Q3 statistic. Second, we applied bifactor models to account for the testlet effect in the responses, as this effect is modeled as an additional latent variable in a factor model. Results support the presence of local dependence in two of the four MDA prompts, and the use of the restricted bifactor model to account for the testlet effect in the responses. Modeling the testlet effect through the restricted bifactor model supports a scoring inference in a validation argument framework. Implications are discussed.